PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - MA’SUM AMIN (Universitas Negeri Jakarta, 2011)
The objective of the research is to determine the effect of leadership style and work motivation on employee performance. The research was conducted at Dinas Pembinaan Mental TNI-AD in Jakarta, 2010 with n=66 selected randomly. The result of research are as follows: (1) there is significant direct effect of leadership style on employee performance at Dinas Pembinaan Mental TNI-AD in Jakarta; (2) there is significant direct effect of work motivation on empoyee performance at Dinas Pembinaan Mental TNI-AD in Jakarta; and (3) there is significant direct effect of leadership style on employee’s work motivation at Dinas Pembinaan Mental TNI-AD in Jakarta. Based on the result of research, the employee performace at Dinas Pembinaan Mental TNI-AD in Jakarta could be enhanced by increasing leadership style and work motivation as significant determinant factors.